Impact of Corporate Governance on Performance of Selected Commercial Banks in Bangladesh: A Comparative Approach - Hossain, Tarik (Journal of Asian Business Strategy, 2022)
This study tries to determine the impact of Corporate Governance (CG) on the performance of Commercial Banks (CB) in Bangladesh. Data are collected from different banks listed under DSE for the period starting from 2015 to 2020. For analyzing the data and testing hypothesis Pearson’s correlation and OLS regression models are used to assess the relationship among the performance of the banks and CG related predictor variables like Board Size (BS), Board Independence (BI), Audit Committee (AC), Risk Management Committee (RMC), and some control variables like Firm Age (FA), Firm Size (FS) and Market Capitalization (MC). The regression analysis results showed a mixed result. The BS and BI are significantly affirmatively related with ROE and positively correlated with ROA. The BS is affirmatively related with Tobin’s Q, but BI is significantly negatively related. No significant positive connection is found between the AC, RMC and ROE, ROA. The RMC is significant affirmatively related with Tobin’s Q, but no significant association between the AC and Tobin’s Q. The theoretical part of this paper has focused about a brief discussion about different variables related with Corporate Governance. The empirical part is based on a survey made on twenty commercial banks listed with DSE.